ZANU(PF)'s Survival Strategies and the Co-option of Civil Society, 2000–2018. Issue 1 (2nd January 2023) - Ndawana, Enock; Hove, Mediel
Abstract : The Zimbabwe African National Union (Patriotic Front) (ZANU[PF]) regime's survival strategies have been misleadingly presented as relying mainly upon political violence. This neglects analysis focusing on the ZANU(PF) regime's non-violent survival strategies, which have also been key to its longevity. While a growing body of literature discusses ZANU(PF) non-violent strategies, including patriotic history, cultural nationalism and provision of land for housing, it has missed much of what has kept ZANU(PF) in power. The existing studies failed to go beyond the idea that ZANU(PF) actors are deeply cynical and only interested in 'power', not 'believers' in their own ideology or responsive to people's needs. Using the cases of ZANU(PF)'s creation and co-optation of civil society organisations that challenge 'genuine' ones for advocacy space, especially labour unions and students' unions between 2000 and 2018, this study makes a twofold contribution to the literature on ZANU(PF)'s political survival. It demonstrates the importance of civil society engagement as a non-violent strategy in ensuring ZANU(PF)'s political survival and that ZANU(PF)'s political project is ideological in addition to being about staying in power. The article concludes that ZANU(PF)'s strategies in relation to civil society were equally critical for the regime's survival in that they necessarily complemented the violent strategies and worked in its favour by disorienting citizen objections and mobilising popular support.